Exploring teleparallel dark energy - Otalora Patiño, Giovanni [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the present thesis we study the cosmological dynamics of the dark energy component of the Universe in the context of the Teleparallel Equivalentof General Relativity, also known as Teleparallel Gravity. It has been proposed recently the existence of a nonminimal coupling between a scalar ?eld (quintessence or tachyon) and gravity in the framework of Teleparallel Gravity, motivated by similar constructions in the context of General Relativity. By generalizing and studying the dynamics of these models, we ?nd interesting and viable cosmological solutions. Then we propose a new model in which the four-derivative of the scalar ?eld of dark energy is non-minimally coupled to vector torsion. This kind of coupling is grounded on the fact that in Teleparallel Gravity a scalar ?eld as a particle of spin zero couples to torsion through its four-derivative, which is a vector ?eld. Differently from the old teleparallel dark energy scenario, this new model is conceptually consistent with the precepts of Teleparallel Gravity, and has no equivalent in the General Relativity context

Nesta tese fazemos um estudo da dinâmica cosmológica da energia escura do Universo, usando o contexto do Equivalente Teleparalelo da Relatividade Geral, também conhecido como Gravitação Teleparalela. Recentemente têm sido propostos diversos modelos com acoplamento não-minimal entre um campo escalar (quintessência ou taquion) e a gravitação, usando o contexto do teleparalelismo, motivados por construções semelhantes no contexto da Relatividade Geral. Generalizando e estudando a dinâmica desses modêlos, encontramos soluções interessantes cosmologicamente viáveis. Em seguida, propomos um novo modêlo no qual a derivada do campo escalar que representa a energia escura se acopla não-minimalmente com a torção vetorial. Esse tipo de acoplamento é inspirado no fato que, no contexto teleparalelo um campo escalar se acopla com a torção através de sua derivada, a qual é um campo vetorial. Diferentemente dos modelos mais antigos de energia escura teleparalela, este novo modêlo é conceitualmente consistente com os preceitos da teoria teleparalela, e não possui equivalente no contexto da Relatividade Geral
Keywords: Gravitação; Energia escura (Astronomia)